Assault–related sharp force injury among adults in Scotland 2001–2013: Incidence, socio-demographic determinants and relationship to violence reduction measures. (May 2019) - Goodall, Christine A.; MacFie, Fiona; Conway, David I.; McMahon, Alex D.
Abstract: Background: The number of patients with assault-related sharp force injury has declined in recent years in Scotland. This study aimed to determine the incidence of these injuries over time and to explore their key socio-demographic determinants. Methods: Routinely collected coded hospital admission data for the time period 2001–2013 were used to calculate annual incidence rates by age-group, gender, geographical region, and area-based Scottish Index of Multiple Deprivation using midyear population estimates. A Poisson regression analysis model was developed including the variables: age-group, gender, year, geographical region, and deprivation quintile. The data were compared with available published crime data. Results: The incidence of sharp force injury showed an ongoing decline between 2001 and 2013. The fall was greatest among young people and in the West of Scotland and mirrored the reduction in weapons and knife related offences. The relative risk of sustaining a sharp force injury was greatest for younger age-groups, among males, and in those resident in the West of Scotland and in areas of socioeconomic deprivation. Conclusions: There already exist a range of violence prevention measures in Scotland, but in order to further reduce the inequality associated with sharp force injury, interventions should be further targeted to working with younger men from deprived communities of Scotland. Highlights: Regression based analyses show that the incidence of assault-related sharp force injury in Scotland fell significantly between 2001-2013. Although the incidence fell most among young people in the West, young males from areas of social deprivation in the West remained most at risk. From 2001-2014 trends in weapons offences in the West of Scotland mirrored the trend in assault-related sharp force injury The fall in assault–related sharp force injury was examined in the context of violence reduction measures introduced during that time period. Targeted interventions are needed to further reduce assault-related sharp force injury among the most at risk groups.